Prevalence of Multiple Drug-Resistant Bacteria in the Main Campus Wastewater Treatment Plant of Wolaita Sodo University, Southern Ethiopia - Chimdesa Adugna; Krishna Moorthy Sivalingam (International Journal of Microbiology)
Wastewater treatment plants (WWTPs) are important reservoirs for the development of drug resistance and a potential route for the dissemination of antibiotic resistance genes (ARGs) in the environment. One of the most serious challenges in Ethiopia is the widespread emergence of antibiotic resistance among bacterial pathogens. The bacteria were isolated between September 2018 and May 2019 from the main campus of Wolaita Sodo University in Southern Ethiopia. Using an enrichment process and selective media isolation, 380 wastewater treatment plant samples were collected and screened for the presence of various bacterial isolates. Of a total of 380 wastewater treatment samples, 136 were isolated. Positive prevalence was documented in 136 sample isolates of bacteria from six genera. Escherichia coli 34 (8.94%), Salmonella spp. 15 (3.94%), Shigella spp. 32 (8.42%), Staphylococcus aureus 23 (6.05%), Pseudomonas aeruginosa 21 (5.52%), and Proteus spp. 11 (2.89%). The general prevalence of bacterial isolates was assessed, and 136 (37.58%) samples tested positive for culture. Furthermore, isolates were used to determine sensitivity/resistance patterns using the Kirby–Bauer disc diffusion method and the agar well diffusion technique, respectively. Multiple drug resistance isolates and multiple values of the antibiotic resistance index were evaluated and recorded according to the resistant pattern. Some organisms were sensitive to sparfloxacin and tobramycin, while Staphylococcus aureus was sensitive to methicillin and others showed the highest resistance. At least four of the seven antibiotic classes were found to be resistant to multiple drug resistance isolates, and some classes of antibiotics were found to be highly sensitive to these isolates. Multiple antibiotic resistance index values ranged from 0.37 to 0.75, with Salmonella spp., Shigella spp., and Staphylococcus aureus having the highest score values. The current study has shown that some of the bacterial isolates were resistant to common antibiotics. Therefore, it is recommended that the emergence of multiple drug resistance increased rapidly, pathogenic bacteria inappropriate treated wastewater treatment plant systems were continuously contaminated, and bacterial resistance increased day by day as a result of environmental factors. As a result, due to the serious challenges facing the community’s health, multiple drug-resistant prevention and control strategies must be implemented.